The Effect Of Employee Relations and Motivation on Employee Job Satisfaction with Workvariables as Intervention Environmentat The Regional Bpjs Employment West Sumatra - Emil Febrianto; Kiki Farida Ferine; Elfitra Desy Surya (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of employee relationships and motivation on employee job satisfaction with the work environment as an intervening variable at BPJS Ketenagakerjaan in the West Sumatra Region. This study uses an associative quantitative approach with a sample of 100 employees from BPJS Ketenagakerjaan offices located in Solok, Bukittinggi, and Padang. The sampling technique used in this study is saturated sampling, where the entire population is used as the research sample. Data were collected through questionnaires. The data analysis method used in this study is Structural Equation Modeling (SEM) with Partial Least Square (PLS) through SmartPLS software. The results of this study are expected to provide information regarding the influence of employee relationships and motivation on job satisfaction, as well as test the mediating role of the work environment on this relationship. This research contributes to the development of human resource management, particularly in creating a conducive work environment and increasing job satisfaction within public service institutions.